2000
DOI: 10.1177/107754630000600802
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Simulations of Linear and Nonlinear Aeroelastic Behavior

Abstract: A method for simulating unsteady, nonlinear, subsonic aeroelastic behavior of an aircraft wing is described. The flowing air and deforming structure are treated as the elements of a single dynamic system, and all of the governing equations are integrated numerically, simultaneously, and interactively in the time domain. The authors' version of the general nonlinear, unsteady, vortex-lattice method is used to predict the aerodynamic forces; a linear finite-element model of the wing, which is derived from MSC/NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…8 (V ∞ = 100 m/s), this common frequency dominates the motion of all modes and the response is clearly unstable. The general form of the curves seems to be in agreement with similar simulations (Preidikman and Mook, 2000), but because the structures are completely different it is impossible to have a quantitative comparison.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…8 (V ∞ = 100 m/s), this common frequency dominates the motion of all modes and the response is clearly unstable. The general form of the curves seems to be in agreement with similar simulations (Preidikman and Mook, 2000), but because the structures are completely different it is impossible to have a quantitative comparison.…”
Section: Resultssupporting
confidence: 72%
“…As the dependence of the time interval for the numerical stability is a characteristic of the predictor-corrector methods (Hughes, 1987), one of the options to improve the presented numerical model is the automation of the time interval choice, or the use of a different numerical method to integrate the equation of motion. It is important to point that predictor-corrector methods were also employed by Strganac and Mook (1990) and Preidikman and Mook (2000) in similar aeroelastic models, but no mention was made about problems with numerical instability. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UVLM [12][13][14] employed here solves for incompressible unsteady aerodynamics over a flexible thin wing with its shed free wake in the time domain. The thin-wing surface is represented by a sheet of distributed vorticities for which the strengths together with those of the wake sheet vorticities are solved simultaneously at each time step.…”
Section: A Description Of Uvlmmentioning
confidence: 99%
“…Mook et al [19][20][21] indicated that the aerodynamic nonlinearities alone could be responsible for limit cycle oscillations. Patil et al [22] used geometrically exact structural analysis and finite state unsteady aerodynamic with stall.…”
Section: Background and Motivationmentioning
confidence: 99%